Alterations in Serum SOD and CAT Levels in Patients with Breast Cancer - kumar and T. Raghava Rao, G. Krishna Veni*, B. Usha, D. Muni (Journal of Experimental Sciences, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> Breast cancers are potentially life-threatening malignancies in women. Development of cancer produces oxidative stress, which increases with disease progression. Hence, studies on antioxidants may be the most promising area of research for this clinical menace. We analysed serum superoxide dismutase (SOD), catalase (CAT) in women with breast cancer. The changes in the levels of serum superoxide dismutase and catalase are measured in breast cancer patients to assess the oxidative stress. A significant increase in the level of superoxide dismutase and a lower catalase activity was observed in all the three categories of breast cancer patients compared to normal individuals. The results suggested that high ROS production supports the oxidative stress in breast cancer. So, the treatment with antioxidants in the initial stages of the disease may be useful as secondary therapy.